2016
DOI: 10.1089/ten.tec.2015.0334
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Flow Regulation of Revascularization and Cellular Organization in a Bioengineered Liver Platform

Abstract: Overall, we were able to unveil the potential central role of discrete mechanical stimulation through the NO pathway in the revascularization and cellular organization of a bioengineered liver. Last, we propose that this organ bioengineering platform can contribute significantly to the identification of physiological mechanisms of liver organogenesis and regeneration and improve our ability to bioengineer livers for transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 41 publications
(53 reference statements)
2
20
0
Order By: Relevance
“…However, one may expect that the endothelial cells lining up the liver scaffold vasculatures would still experience the high shear stress from the abdominal arterial flow. This is relevant as it has shown that high shear stresses negatively influenced the viability of cells within the liver scaffolds . This report may explain the large amount of the caspase‐3+ endothelial cells observed in the re‐endothelialized liver scaffold transplants (Fig.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, one may expect that the endothelial cells lining up the liver scaffold vasculatures would still experience the high shear stress from the abdominal arterial flow. This is relevant as it has shown that high shear stresses negatively influenced the viability of cells within the liver scaffolds . This report may explain the large amount of the caspase‐3+ endothelial cells observed in the re‐endothelialized liver scaffold transplants (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…A variety of cell types have been examined for liver scaffold recellularization, including immortalized cells, adult primary cells, fetal cells, mesenchymal stem cells and induced pluripotent stem cells . Many studies have shown that recellularized liver scaffolds perform hepatic specific functions in vitro .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To create human liver organoids, we used our previously described decellularization method to fabricate liver ECM scaffolds and then sectioned the scaffold and seeded sections (8‐mm ECM discs) with hFLPC cultures that contained liver stromal (25%‐40%) and endothelial (5%‐15%) cells (http://onlinelibrary.wiley.com/doi/10.1002/hep.29483/suppinfo). Within 2‐3 weeks postseeding and culture in LDM, the cells and ECM self‐assembled into 3D organoid structures with progressive cellular organization and differentiation (http://onlinelibrary.wiley.com/doi/10.1002/hep.29483/suppinfo).…”
Section: Resultsmentioning
confidence: 99%
“…15,34 Interestingly, other vascular mediators generated from liver circulation (eg, prostaglandins, nitric oxide, and catecholamines) could also be involved in hepatic growth and maturation, recently shown in a bioengineered liver. 35 …”
Section: In Vivo Liver Maturationmentioning
confidence: 99%